2009
DOI: 10.1002/nur.20336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coping skills training in school‐age children with type 1 diabetes

Abstract: Children with type 1 diabetes are at risk for negative psychosocial and physiological outcomes, particularly as they enter adolescence. The purpose of this randomized trial (n=82) was to determine the effects, mediators, and moderators of a coping skills training intervention (n=53) for school-aged children compared to general diabetes education (n=29). Both groups improved over time, reporting lower impact of diabetes, better coping with diabetes, better diabetes self-efficacy, fewer depressive symptoms, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 53 publications
1
98
1
5
Order By: Relevance
“…Building on this work, Grey et al 42 studied whether providing coping skills training to preadolescent youths with type 1 diabetes would reduce problems as they enter adolescence. The purpose of this randomized trial (n = 82) was to determine the effects, mediators, and moderators of a coping skills training intervention for school-aged children compared to general diabetes education.…”
Section: Evidence For Coping Skills Training With Children and Adolesmentioning
confidence: 99%
“…Building on this work, Grey et al 42 studied whether providing coping skills training to preadolescent youths with type 1 diabetes would reduce problems as they enter adolescence. The purpose of this randomized trial (n = 82) was to determine the effects, mediators, and moderators of a coping skills training intervention for school-aged children compared to general diabetes education.…”
Section: Evidence For Coping Skills Training With Children and Adolesmentioning
confidence: 99%
“…CST teaches cognitive behavioral skills such as problem solving, effective communication, conflict resolution, stress management, and behavior modification (Grey et al, 2009;Velsor-Friedrich et al, 2012). Institutional review board approval from authors' university and public school review board was obtained prior to study initiation.…”
Section: School-based Asthma Programmentioning
confidence: 99%
“…Glycemic control was not focused on as the primary outcome variable in every trial that reported significant improvements. The majority of trials demonstrated a significant effect on the improvement of coping, self-management behavior [36,38 ,40, 42,44], and diabetes-related self-efficacy [36,39,42,44,45] even when these were focused on as secondary outcome variables. Compared with control conditions, intervention participants improved significantly in terms of physical activity [38 ,44,45], awareness of hypoglycemia [39,44], HRQoL [37,38 ,42], and adherence to treatment [39,40].…”
Section: Diabetes Mellitus: a Public Health Problemmentioning
confidence: 99%
“…In six RCTs glycemic control as measured by HbA1c was examined as the primary outcome [37,38 ,40,41,43 ,44]. In addition, changes in coping and self-management behavior [36,37,42], diabetes-related self-efficacy [36,39,42,44,45], treatment adherence [39,40], HRQoL [37,38 ,41,42,43 ], physical activity [38 ,43 ,44,45], dietary behavior [38 ,39,43 ], and BMI [40,42,43 ] were evaluated as treatment outcomes. Medical outcomes included blood pressure [38 ,43 ], cholesterol [38 ,43 ], and the frequency of hypoglycemia [39,41,43 ], whereas depressive symptoms and diabetes-related distress [39,40,43 ,44] were evaluated as psychological outcomes.…”
Section: Diabetes Mellitus: a Public Health Problemmentioning
confidence: 99%
See 1 more Smart Citation